APPLICATIONNEURAL NETWORK PROBABILITYIN THE CLASSIFICATION OF BANANA FIT FOR EXPORT - Reni Aryanti; Zulfahmi Syahputra; Wirda Fitriani (Sean Institute, 2022)
As food, bananas are a source of energy (carbohydrates) and minerals, especially potassium. Almost all ripe bananas are yellow, although some are orange, red, green, purple or almost black. In agriculture, to determine the type of fruit and the quality of the fruit, it can be determined by checking the size of the fruit, the shape of the fruit and the color of the skin of the fruit.Classification of types of bananas using the neural network probability method(PNN) as a method of classifying types of bananas that are suitable for export and suitable for domestic consumption with 750 training data and 250 testing data with categories of three types of bananas namely Ambon bananas, Barangan bananas and Kepok bananas and produces an accuracy of 85.2 %.